The future of sustainable development and agrobiodiversity in Tanzania and Uganda - Kozicka, Marta; Enahoro, Dolapo K.; Groot, Jeroen C.J.; Rich, Karl M.; Gotor, Elisabetta (Center for Open Science, 2021)
This document is part of a series of short papers on “The Future of X”, produced as part of foresight-related research supported by the CGIAR Research Program on Policies, Institutions, and Markets, and edited by Keith Wiebe (IFPRI) and Steven Prager (Alliance of Bioversity and CIAT). These short papers are intended to provide a focused, forward-looking perspective on key issues to support discussion on food, land, and water systems transformation. We thank two anonymous reviewers for their comments on an earlier draft. This is an accepted version presented as a pre-print. It is currently undergoing final revision, editing, and production. A final version will be made available at http://foresight.cgiar.org.